An Inquiry into the Relation between the Young Rawls's Theological Ethics and his Second Principle of Justice in the Later Works - N. Limahekin, Antonius Bastian (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2011)
With regard to the connectedness of the political subject and its community, Rawls’s theory of justice has often been criticised by the thinkers whose thoughts are oriented towards community. Rawls was considered to have impoverished the political subject by treating it as floating individual, rooted out of its foundation in community. In the middle of the debate that was still going on around this matter, an edited version of the young Rawls’s thesis was published. Despite the fact that this did not help much in saving this philosopher from the criticism by the communitarian thinkers because of his final preference that leaned towards political conception, the ethical theological work at least showed that communitarian position was once chosen by Rawls. By reading and comparing and juxtaposing this work with his later works, we can see that Rawls, the proposer of justice as fairness, did not completely drop his younger thought on person and community. In other words, between the theological ethics of the Young Rawls and the justice theory of Rawls there is a continuity of thought. This can be sensed among other in his basic assumptions on the individual and the society, those he implies in his argument on the ‘difference principle’ and the ‘principle of equal opportunity’. Keywords :*person *personality *individual *community *society *difference principle *principle of equal opportunity *fairness *equality *equality in community *civic friendship *interpersonal*relationship *comprehensive doctrine